Implementation of Social Jurisprudence by KH Sahal Mahfudh in the Practice of Family Planning Program in Pagertanjung Jombang - Jalaludin, Faqih; Zahro, Ahmad (State of Islamic Institute Langsa, 2023)
A happy family is created by a harmonious marriage and household relationship. It will be more perfect if the household is blessed with a baby who will be the next generation. KH. Sahal Mahfudz offers a thought solution to answer how this family planning program should be a way out for household life according to the current socio-economic conditions of society. Through his social fiqh thoughts, KH. Sahal Mahfudh, the writer wants to know how the social jurisprudence perspective of KH. Sahal Mahfudz on the Family Planning Program and the Implementation of Social Jurisprudence KH. Sahal Mahfudz in Pagertanjung Ploso Village, Jombang. This research is a type of qualitative research, data taken systematically from the field and literature. The data will then be viewed and measured using the perspective of KH's social jurisprudence. Sahal Mahfudh. As a result, the social jurisprudence of Kh. Sahal Mahfudh was able to encourage people to be self-aware of the importance of maintaining economic health and family resilience. Kiai Sahal further explained that there was no prohibition on family planning in religion. If the Shari'a recommends maintaining family resilience, then family planning is a very appropriate program and Pagertanjung Village can become a pilot village through its family planning and community empowerment programs.